Effects of collaborative learning technique and mathematics anxiety on mathematics learning achievement among secondary school students in Gombe State, Nigeria / Muraina Kamilu Olanrewaju and Yusuf Suleiman - Olanrewaju, Muraina Kamilu; Suleiman, Yusuf (Universiti Teknologi MARA, 2019)
Mathematics is one of the subjects that is taken very seriously in the school system, irrespective of country or level of education. This study therefore examined the effects of collaborative learning technique and Mathematics anxiety on Mathematics learning achievement of secondary school students in Gombe State, Nigeria. Pretest-posttest, control group quasi-experimental design with a 2x2 factorial matrix was used in the study. Multi-stage sampling technique was used in sampling participants from four local government areas in the state. The respondents were measured with validated scale of 0.84 reliability coefficient research instrument and the data obtained was analyzed using independent samples t-test statistical analysis. Two (2) research hypotheses were formulated and tested at 0.05 level of significance. The results showed that there was a significant difference in the Mathematics learning achievement of secondary school students exposed to collaborative learning technique and those in the control group (t= 58.75; p<0.05) and there was a significant difference in the Mathematics learning achievement of secondary school students with high Mathematics anxiety and those with low Mathematics anxiety (t= 38.41; p<0.05). In view of these findings, the study recommends that educational stakeholders should intensify their effort to organize conferences on the implications of collaborative learning technique for effective interventions towards enhancing Mathematics learning achievement among secondary school students.